2020
DOI: 10.1002/bjs5.50302
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the impact of postoperative infective complications on oncological outcomes in colorectal cancer surgery

Abstract: Background: Cancer outcomes are complex, involving prevention, early detection and optimal multidisciplinary care. Postoperative infection and surgical site-infection (SSI) are not only uncomfortable for patients and costly, but may also be associated with poor oncological outcomes. A meta-analysis was undertaken to assess the oncological effects of SSI in patients with colorectal cancer. Methods: An ethically approved PROSPERO-registered meta-analysis was conducted following PRISMA guidelines. PubMed and Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 71 publications
1
24
0
2
Order By: Relevance
“…Anastomotic leakage has a significant negative impact on disease-free survival, overall survival and local recurrence [ 5 , 6 ]. A meta-analysis including a total of 154,981 patients showed that anastomotic leakage had a negative impact on overall survival [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anastomotic leakage has a significant negative impact on disease-free survival, overall survival and local recurrence [ 5 , 6 ]. A meta-analysis including a total of 154,981 patients showed that anastomotic leakage had a negative impact on overall survival [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inflammation caused by AL contributes to tumor escape immune surveillance by suppressing T cell [ 14 , 15 ]. Several meta-analyses have shown that AL decreases overall survival and disease-free survival and increases the risk of cancer-related death in rectal cancer patients [ 16 18 ]. Many factors may affect postoperative complications, including age, sex, tumor location, and diabetes mellitus [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, performance improvement programmes are focusing on optimising laparotomy outcomes in order to reduce morbidity and mortality, particularly in relation to surgical site infection [ 4 , 5 ]. SSIs are not only a source of both inconvenience and added cost, but they may also result in adverse oncological outcomes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%